Simultaneous RP-HPLC quantification of curcumin, silymarin, and piperine: Method development and validation - Misbah Sultana Abdul Kausar Badewale; Varsha Siddheshwar Tegeli (Creative Pharma Assent, 2026)
Background: Herbal formulations containing multiple phytoconstituents require analytical methods that can simultaneously determine structurally diverse compounds with adequate selectivity and precision. Curcumin (CUR), Silymarin (SLY), and Piperine (PIP) are widely incorporated into polyherbal preparations owing to their clinically studied pharmacological actions. Ensuring consistent quality of such formulations requires a validated, reliable chromatographic procedure. Methodology: A reverse-phase HPLC method was established for concurrent estimation of CUR, SLY, and PIP using an Agilent Zorbax Bonus RP column (250 × 4.6 mm, 5 μm). Separation was achieved with a mobile phase of 0.1% perchloric acid and acetonitrile (45:55, v/v) at 1.0 mL/min, with UV detection at 215 nm. The method was evaluated for specificity, precision, linearity, accuracy, and sensitivity using standard validation criteria aligned with internationally accepted analytical quality guidelines. Results and Discussion: The analytes were successfully separated within 11 minutes, with retention times of 4.09 min for Silymarin, 7.39 min for Piperine, and 10.25 min for Curcumin. System precision demonstrated %RSD values below 0.21% for all analytes. Recovery values across 80–120% concentration levels were close to 100%, with %RSD <0.5%, reflecting excellent accuracy. Calibration curves exhibited strong linearity (R² = 0.999). The method demonstrated high sensitivity with LOD values below 2 µg/mL and LOQ values below 6 µg/mL for each compound. Both intra-day and inter-day evaluations showed %RSD <0.4%, confirming robust reproducibility. Robustness testing with small, deliberate variations showed %RSD <1.5%, confirming the method's reliability. Conclusion: The developed RP-HPLC protocol offers a selective, reproducible, and sensitive analytical approach suitable for simultaneous quantification of SLY, PIP, and CUR in combined herbal matrices.